From Novel to Film: Religious Pluralism in The Da Peci Code, Rosid & Delia, and 3 Hati 2 Dunia 1 Cinta - Ahfa Rahman Syah (Buletin Al-Turas, 2026)
Purpose Religious pluralism is a key aspect of Islam Nusantara, aiming to accommodate and inspire diversity and differences, including through literature. This article examines how religious pluralism is represented in the novels The da Peci Code and Rosid & Delia (2008) and its transformation in the film 3 Hati 2 Dunia 1 Cinta (2010). Methods This study employs a qualitative approach with descriptive analysis through close reading of narrative elements in the novels and scenes and dialogues in the film. The theoretical framework includes indifferent and non-indifferent religious pluralism and the theory of media adaptation. Results/Findings The analysis reveals that the blending of attributes and culture, interfaith romance, and exchange of terminology are key aspects employed to promote religious pluralism. In the novels, these three aspects are framed within the context of indifferent pluralism, suggesting that all religious beliefs and ideologies possess equal truth. In the film, these aspects are transformed into non-indifferent pluralism, emphasizing sociological dimensions of religions and social roles such as tolerance, collaboration, and synergy. Conclusion The findings indicate the dynamics and strategies by which literature and film contribute to promoting religious pluralism in alignment with the social and psychological conditions of their audiences. This phenomenon also reflects the freedom to engage in cultural practices, which forms part of democratic practice in Indonesia.